Determination of blood flow direction using velocity-phase image display with 3-D phase-contrast MR angiography. - Pernicone, J R; Siebert, J E; Laird, T A; Rosenbaum, T L; Potchen, E J (American Journal of Neuroradiology, 1992)
The authors describe their use of phase-contrast MRA to depict vascular anatomy and to define the direction of blood flow. Documentation of flow reversal can provide information regarding prognosis and can facilitate surgical planning. The technique requires no additional scan-time.